2010
DOI: 10.1007/s00464-010-1201-0
|View full text |Cite
|
Sign up to set email alerts
|

Maximum tensile force of different suture techniques in reconstruction of the renal remnant after nephron-sparing surgery

Abstract: The data suggest that of all tested suture techniques, the horizontal mattress suture provides the best adaptation strength before the suture tears through the renal parenchyma/capsule. Furthermore, it is recommended that the kidney capsule be included in the reconstructive suture because this significantly contributes to the safety of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Two different groups demonstrated that the absence of renal capsule at the moment of renorrhaphy severely weakens parenchyma strength, while the presence of it helps withstand pressure from the suture allowing for adequate hemostasis. 8,14 In essence, capsular indemnity is vital for quality suturing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two different groups demonstrated that the absence of renal capsule at the moment of renorrhaphy severely weakens parenchyma strength, while the presence of it helps withstand pressure from the suture allowing for adequate hemostasis. 8,14 In essence, capsular indemnity is vital for quality suturing.…”
Section: Discussionmentioning
confidence: 99%
“…To this respect, tensile strength has been compared between normal and decapsulated human kidneys. 8 Decapsulated kidneys resist between 43% and 63% less than normal ones deeming renorrhaphy a very challenging task with the inherent risk of severe surgical bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Several surgical methods exist for achieving hemostasis following tumor enucleation including: the traditional closure of the parenchymal defect with suture ligasure by application of topical absorbable hemostats such as oxidized regenerated cellulose, gelatin, collagen and liquid fibrin sealants have been employed to decrease intraoperative renal ischemic time, provide rapid hemostasis and improve visualization of the surgical field [5,[9][10][11][12]. In our series we have used BG to fill the parenchymal defect.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to conventional surgical techniques for hemostasis, the use of a Surgisis ® membrane does not compromise blood flow in the parenchymal resection margin, since no parenchymal tissue has to be gathered or folded. The running suture technique mimicking the fixation of a drumhead (Figure 2) additionally enables maximal stability and prevents tearing of the suture from the renal capsule [26]. Another great advantage of this technique is the establishment of a phantom or placeholder volume beneath the membrane (Figure 1) which enables the establishment of homogenous pressure on the resection area.…”
Section: Discussionmentioning
confidence: 99%